Opportunities and challenges of green logistics in Singapore - Zhuang, Christal Lee Er (Nanyang Technological University, 2022)
The importance of the logistics industry is visible through the support and facilitation it has provided for the growth of many economies in the world. However, it has also brought damaging effects on the environment giving rise to the concept of green logistics and specifically urban logistics. These new concepts have been implemented by many countries in the world including Singapore. Nonetheless, there is a lack of evaluation of the potential and problems of implementing green logistics in Singapore. An overview of the role and significance of green logistics is first provided before moving deeper into its importance for Singapore. Case studies of various countries implementing green logistics were also discussed. To provide a deeper analysis of the topic of green logistics in Singapore, the topic was divided into three contributing factors, namely transportation, warehousing, and packaging. The focus of this report will be on the packaging of green logistics. Packaging is commonly used to protect goods and make them easier to transport, however it has brought upon issues that will discussed on a global and national level. Problems such packaging waste and leakage of plastic into the oceans are growing at an alarming rate supported by the growth in international trade and e-commerce demand. Singapore and numerous countries in the world have been implementing measures and solutions to promote green packaging. The lack of impactful measures undertaken by the Singapore government was determined to be the reason for the slow progression of green packaging in Singapore. To grasp what is needed to improve this situation, qualitative and quantitative data was collected for analysis and cross-referencing to deepen the understanding of the situation thus forming the basis for recommendations. The findings indicated that cost is the primary factor that deters the progress of green logistics in Singapore. Other factors such as organisation culture, company strategy, resources, capability, are motivating factors that could impede the speed of change towards going green. Specifically, for packaging, the availability of green materials and cooperation between suppliers and customers will determine the rate of implementation of green packaging in Singapore. The recommendations suggested were in response to the challenges discovered and to support and boost the switch to green packaging in Singapore. The goal of the suggestions is to facilitate the process of shifting to sustainable logistics and packaging. Limitations of the recommendations and of this report are also included to provide for a well-rounded analysis for the readers.